The Effect of Jigsaw Cooperative Learning on Reading and Writing Skills of B1 Level High School Students - Wijaya, Berlianti Sonia; Ratih, Koesoemo (Jurnal Pendidikan Bahasa Inggris Proficiency, 2026)
This study investigates the effectiveness of the Jigsaw Cooperative Learning model on the English reading and writing skills of tenth-grade students at SMA Negeri 1 Kartasura, aligned with the CEFR B1 standard. A quasi-experimental design was employed, involving an experimental group and a control group, with data collected through pretests, posttests, and student perception questionnaires. Statistical analysis using an independent samples t-test yielded a p-value of 0.000, indicating that the Jigsaw model significantly improves reading and writing skills compared to conventional methods. The experimental group achieved greater score improvements, facilitated by peer tutoring and the distribution of responsibilities within expert and home groups. Questionnaire results further revealed that students responded positively, demonstrating enhanced enthusiasm, self-confidence, and active engagement in classroom activities, although some required additional guidance to optimize individual responsibilities. These findings suggest that the Jigsaw model is an effective instructional strategy for integrating language skills, fostering collaborative learning, and supporting CEFR B1 proficiency within the 2025 curriculum. This study recommends adopting the Jigsaw model to create a more interactive, self-directed, and outcome-focused learning environment.